Pengaruh Strategi Pembelajaran dan Kecerdasan Interpersonal terhadap Hasil Belajar PKn Siswa SMP - Sunanto - (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2015)
The research was aimed to get information about learning strategies based on interpersonal intelligence on civics learning outcomes. The research was conducted on Au- gust until October 2012, at SMP Negeri 10 Bandar Lampung. The researh method used ex- perimental with treatment design by level 2 x 2. The results of research shows: (1) students’ civics learning outcomes who learned by using cooperative learning strategy are higher than those who learned by self – study learning strategy; (2) there is interaction effect be- tween learning strategies and interpersonal intelligence on civics learning outcomes; (3) students’ civics learning outcomes who have high interpersonal intelligence taught coop- erative learning strategy are higher than taught self-study learning strategy.